2018
DOI: 10.18500/2304-9790-2018-7-1-4-15
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Personal Factors for Successful Learning of a Foreign Language by Linguistics Students

Abstract: Бериша Надежда Сергеевна, магистр лингвистики, соискатель, кафедра социальной и дифференциальной психологии, Российский университет дружбы народов, Москва, Рос-сия, 1032140379@rudn.university Новиков Алексей Львович, кандидат филологических наук, доцент, кафедра общего и русского языкознания, Российский университет дружбы народов, Москва, Россия, novikov_al@rudn.university Новикова Ирина Александровна, кандидат психологических наук, доцент, кафедра со-циальной и дифференциальной психологии, Российский универси… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 11 publications
1
14
1
Order By: Relevance
“…However, a study of Russian linguistics students' academic achievements in different subjects showed that none of the FFM traits are associated with a student's final grades in English (as the "first" and mandatory FL), while conscientiousness, extraversion, and neuroticism are correlated with the final grades for their "second" elective FL [18]. In our previous study, we found that openness is most closely correlated with academic achievements in English as an FL among Russian linguistics students [21]. In Russian psychology, a large number of FLA studies have been carried out using the System-Functional Model of personality traits developed by Krupnov [22].…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…However, a study of Russian linguistics students' academic achievements in different subjects showed that none of the FFM traits are associated with a student's final grades in English (as the "first" and mandatory FL), while conscientiousness, extraversion, and neuroticism are correlated with the final grades for their "second" elective FL [18]. In our previous study, we found that openness is most closely correlated with academic achievements in English as an FL among Russian linguistics students [21]. In Russian psychology, a large number of FLA studies have been carried out using the System-Functional Model of personality traits developed by Krupnov [22].…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies show that openness to experience and especially conscientiousness are significant predictors of academic achievements for most studied subjects, including FL/SL [15][16][17]. Recent Russian research based on the FFM has shown that conscientiousness impacts the academic achievements of Russian university and grade-school students [18][19][20][21]. However, a study of Russian linguistics students' academic achievements in different subjects showed that none of the FFM traits are associated with a student's final grades in English (as the "first" and mandatory FL), while conscientiousness, extraversion, and neuroticism are correlated with the final grades for their "second" elective FL [18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations